Evaluation of drilling by induced delamination of hybrid biocomposites reinforced with natural fibers: a statistical analysis by RSM - Elhadi, Abdelmalek; Amroune, Salah; Slamani, Mohamed; Jawaid, Mohammad; Koklu, Ugur; Bidi, Tarek (SAGE Publications Ltd, 2024)
Studying the drilling of a hybrid jute/palm composite material offers significant contributions to sustainable material development. Incorporating renewable jute and palm fibers represents an innovative, eco-friendly approach compared to synthetic composites. This research aims to optimize drilling parameters to reduce defects and evaluate the performance of different drilling tools, crucial for industrial applications. Drilling is performed via three different types of drills bit: High-Speed Steel, HSS-Co5 coated high-speed steel with 5% cobalt, and carbide. The drilling process involves adjusting the feed and rotational speed. Response Surface Methodology (RSM) was used to select drilling settings by validating experimentally obtained data and predicting the behavior of the structure based on cutting circumstances. The findings indicated that the most effective cutting parameters for minimizing delamination are achieved using the HSS drill bit, namely at lower feed and rotational speeds. Delamination remains below the threshold of 1.106 when the feed is 0.04 mm/rev and the rotational speed is 1592 rpm. The analysis of the results obtained using the response surface methodology indicates that the R2 coefficient for cylindricity is 0.96%. In contrast, the rate of delamination is 0.79% and the rate of circularity is 0.89%.